E-Learning in the teaching of history through architecture - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen; Mahmud, Murni (2009)
This paper presents the development of an e-learning application combining virtual reality (VR) and multimedia techniques which features interactive real time walkthroughs of highly accurate 3D architectural and ancient city models for the development of an innovative tool in teaching of history and humanities, cultural knowledge and cultural identity. This research and prototypical development combines multimedia, architectural and information technology specialists. It is an attempt to bring the study of virtual reality computer models within the scope of a humanities field. The ICT application integrates 3D virtual architectural monuments, with a user interface enabling students and teachers to access graphical and textual material, illustrating and exploring the history, evolution, variety, and current range of architectural heritage monuments, the primary objective is addressing the use of multi-media for teaching of history and humanities is focused upon. In addition to providing extensive primary factual information, the interface allows students and teachers to access and study essential elements of history through architecture which difficult to convey using conventional teaching materials. The challenge in virtual reality is how to trade-offs between realism and accuracy, as the constraints of VR are always associated with number of polygon counts and level of details. This paper discusses expected findings in the user evaluation studies on the issues associated with a comparison between learning using traditional approach and using VR